2021
DOI: 10.3389/fmed.2021.673187
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Determinants of Behavioral Responses to the Pandemic of COVID-19

Abstract: Background: Understanding knowledge and behavioral responses to the pandemic of coronavirus disease 2019 (COVID-19) is important for appropriate public health interventions.Objectives: To assess knowledge of COVID-19 and to examine determinants associated with the adoption of preventive health behaviors among future health care providers.Methods: An anonymous online survey was sent out to pharmacy students in high and low-endemic areas of COVID-19 in China. Based on recommendations from the Chinese Center for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In the past 2 years since December 2019, COVID-19, caused by the etiological agent of SARS-CoV-2, has evolved into a global pandemic and a public crisis event, which caused the world to experience a life-changing transition ( 1 , 2 ). Up to 5:08 pm on 10 March 2022, Central European Time, there were 450,229,635 confirmed cases of COVID-19 and 6,019,085 deaths, according to WHO ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past 2 years since December 2019, COVID-19, caused by the etiological agent of SARS-CoV-2, has evolved into a global pandemic and a public crisis event, which caused the world to experience a life-changing transition ( 1 , 2 ). Up to 5:08 pm on 10 March 2022, Central European Time, there were 450,229,635 confirmed cases of COVID-19 and 6,019,085 deaths, according to WHO ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 And an anonymous online survey sent out to 203 pharmacy students in high-and low-endemic areas of COVID-19 in China showed a medium level of knowledge of COVID-19. 17 Another reported an adequate level of knowledge about COVID-19, with no significant differences among the populations in Central China. However, Huynh et al reported that 88.4% of participants had sufficient knowledge regarding COVID-19.…”
Section: Discussionmentioning
confidence: 96%
“…in China,showed a medium level of knowledge of COVID-19 17 . Another reported that an adequate level of knowledge about COVID-19 with no significant differences among the populations in Central China.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, understanding the benefits of using medicinal plants and the disadvantages of not using has increased the individual effectiveness in the positive belief about the use of medicinal plants in prevention of COVID-19. [ 37 38 ] Therefore, it can beneficial to design the appropriate interventions to stablish the educational programs and interventional techniques aiming to increase people awareness and proper use of medicinal plants.…”
Section: Discussionmentioning
confidence: 99%